KORELASI ANTARA RELIGIUSITAS DENGAN GRATITUDE (KEBERSYUKURAN) PADA MAHASISWA PENERIMA BANTUAN BIAYA PENDIDIKAN BIDIKMISI DI UNIVERSITAS PENDIDIKAN INDONESIA - Nida Damia Ramdhani Ali Alfathimy, Nida Damia (2020)
The problems of Bidikmisi students at Indonesia University of Education are low GPA scores, slow completion of studies, and some even cannot complete their studies. That problem can be caused by ungratefulness. One of the factors that causes gratitude is religiosity. For this reason, this study aims to determine how much the relationship between religiosity and gratitude for Bidikmisi students at Indonesia University of Education. The method of this research is correlational research. The subjects in this study were 100 Bidikmisi students studying at Indonesia University of Education. The correlation technique used is the Pearson Product Moment correlation technique. The results of this study indicate that religiosity is significantly correlated with gratitude in Bidikmisi students.